Pengaruh Kepemimpinan Kepala Sekolah dan Profesionalitas Guru Pendidikan terhadap Hasil Belajar Siswa - Imam Tholkhah; Yusfi LR (LPPM Institut Nasional Laa Roiba Bogor, 2019)
ABSTRACTThis study aims to determine the effect of curriculum competence and motivation on studentachievement in the Faculty of Islamic Studies. The form of survey research is quantitative, that is researchconducted to look for the effect of curriculum, lecturer competence and motivation on student achievementin the Islamic Faculty of Tarbiyah Department of Islamic Studies Laa Roiba, Bogor Regency. The researchmethod used in this study is a survey method. This research is correlational because the research seeks toinvestigate the relationship between several research variables namely competence, curriculum andmotivation variables on learning achievement. This correlation study will use correlation and regressionanalysis. In this study there are three independent variables, namely competence (X1), Curriculum (X2),and motivation (X3) to the dependent variable namely learning achievement (Y). The three independentvariables (X1, X2, and X3) are related to the dependent variable (Y). The results showed that there was apositive influence between lecturer competence (X1) on learning achievement (Y). This is indicated by thecorrelation coefficient of 0.921 with the significance of the correlation coefficient of tcount of 3.967 andthe significance of the regression coefficient of Fcount of 51.930 which is very significant at α = 0.05. forthe curriculum (X2) of learning achievement (Y). There is a positive influence. This is indicated by thecorrelation coefficient of 0.914 with the significance of the correlation coefficient of tcount of 8,547 andthe significance of the regression coefficient of Fcount of 51,930 which is very significant at α = 0.05, andfor motivation (X3) for achievement of learning outcomes (Y). This is indicated by the correlationcoefficient of 0.940 with the significance of the correlation coefficient of tcount of 3.189 and the significanceof the regression coefficient of Fcount of 51.930 which is very significant at α = 0.05, while the results of theanalysis of lecturer competencies (X1), curriculum (X2), and motivation (X3) are together on theachievement of learning outcomes (Y) has a significant multiple correlation coefficient with a value of0.858 with the significance of the multiple regression coefficient Fcount 51.930. In this study shows theimportance of lecturer competency, curriculum and motivation variables in an effort to improve studentlearning outcomes and it can be concluded that as an educator must have competence, understand thecurriculum and provide motivation to students, student achievement will increase and vice versa if as aneducator do not have good competence, do not understand the curriculum and lack of motivation tostudents, learning achievement will decrease.Keywords: Effect of Competence, Curriculum and Motivation on Learning Achievement